2019
DOI: 10.3390/min10010003
|View full text |Cite
|
Sign up to set email alerts
|

Critical Elements in Supergene Phosphates: The Example of the Weathering Profile at the Gavà Neolithic Mines, Catalonia, Spain

Abstract: The essential role of Critical Elements (CE) in 21st century economy has led to an increasing demand of these metals and promotes the exploration of non-conventional deposits such as weathering profiles. The present work is focused on the study of a weathering profile located at the Archaeological Park of the Gavà Neolithic Mines, Barcelona, Catalonia, Spain. In the Gavà deposit, acid and oxidising meteoric fluids generated intense weathering during the early Pleistocene, affecting series of Llandoverian black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Supergene mineralization is only hosted in the Silurian series of the Paleozoic basement. These correspond to sulphide-rich black shales of Llandoverian age and interbedded with layers of a few centimeter-thick and nodules of fluorapatite and chert [20,[43][44][45][46]54]. These rocks are pale grayish in the surface outcrop and, below the Quaternary unconformity, they become progressively darker downwards, reaching the original black colour at a depth of 15 m. The variation in colour of the shales has been attributed to the oxidation of the contained organic matter during the interaction with oxidizing acid fluids.…”
Section: Geological Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supergene mineralization is only hosted in the Silurian series of the Paleozoic basement. These correspond to sulphide-rich black shales of Llandoverian age and interbedded with layers of a few centimeter-thick and nodules of fluorapatite and chert [20,[43][44][45][46]54]. These rocks are pale grayish in the surface outcrop and, below the Quaternary unconformity, they become progressively darker downwards, reaching the original black colour at a depth of 15 m. The variation in colour of the shales has been attributed to the oxidation of the contained organic matter during the interaction with oxidizing acid fluids.…”
Section: Geological Settingsmentioning
confidence: 99%
“…In the latter, its characterization and the corresponding study of colours can provide significant data about the source area of archaeological remains and ornaments, among other reasons (e.g., development of exchange networks and construction of cultural identities). Moreover, changes in variscite colour were attributed to the grade of Fe oxidation [20] and could therefore provide information about the level of finding in a single deposit [21]. First works focused on the study of variscite colouration indicated that a typical greenish colour was probably produced by the occurrence of chromophores such as Cr 3+ [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metals (and Ba) are effectively transported as chloride complexes in diagenetic and hydrothermal fluids [78], whereas sulphur is commonly transported as sulphate (SO 4 2− ) complexes during the formation of sandstone-type uranium deposits [58] and many low-temperature hydrothermal deposits [79]. Sulphate complexes can also be effective in the transport of uranium and other critical elements [80,81]. The arrival of hydrothermal fluids to the coal-rich reducing domains triggered a massive precipitation of Cu-V-U-rich minerals, including silicates, sulphides, arsenides and selenides in Eureka.…”
Section: Stage 3: Stratabound Mineralisationmentioning
confidence: 99%
“…The demand for uranium, rare earth and related rare elements (REE) has increased in recent times to meet new technological requirements and this has increased interest in exploration activity for these elements [6][7][8]. More than 1100 uranium and radioactive anomalies and~300 such zones were discovered during earlier Soviet exploration and more recent exploration undertaken by Western companies.…”
Section: Introductionmentioning
confidence: 99%